PENINGKATAN KETERAMPILAN GERAK DASAR LOKOMOTOR MENGGUNAKAN METODE BERMAIN DALAM PEMBELAJARAN PENDIDIKAN JASMANI SISWA KELAS III C SDN KRIAN 3 KABUPATEN SIDOARJO - Ikee Proklamasi Agustini; Agus Tomi; I Nengah Sudjana (Fakultas Ilmu Keolahragaan UM)
Abstract: Based on preliminary observation during Physical Education class in class III C SDN Krian 3 Sidoarjo regency, it is found a problem that the Physical Education learning process had obstacle in terms of teaching and learning due to insufficient facility posessed by the school. There are 20 students (47.62%) from 42 students (100%) who had problem in following learning process because they felt bored in Physical Education class, therefore students suffered from obstacles in improving their basic movement skill. The aim of conducting this study is to solve the problems by implemeting learning methods interesting students which is by using games methods. This study is a classroom action research which gives solution to the problems during learning process and improves learning quality in order to achieve learning goals.Keywords: Locomotor basic movement, games methods, Physical Education